Secrecy Outage Analysis of Mixed RF-FSO Systems With Channel Imperfection - Hongjiang Lei; Haolun Luo; Ki-Hong Park; Zhi Ren; Gaofeng Pan; Mohamed-Slim Alouini (IEEE Photonics Journal)
We analyze the secrecy outage performance of a mixed radio frequency-free space optical (RF-FSO) transmission system with imperfect channel state information (CSI). We deal with a single-input multiple-output wiretap model, where a base station (works as the relay) forwards the signal transmitted from a user (source) to a data center (works as the destination), while an eavesdropper wiretaps the confidential information by decoding the received signal. Both the relay and the eavesdropper are armed with multiple antennas, and maximal ratio combining scheme is utilized to improve the received signal-to-noise ratio (SNR). The effects of imperfect CSI of the RF link and the FSO link, misalignment, detection schemes, and relaying schemes on the secrecy outage performance of mixed RF-FSO systems are studied. First, the cumulative distribution function and probability density function of FSO links with pointing error and two different detection technologies are derived. Then, we derive the closed-form expressions for the lower bound of the secrecy outage probability (SOP) with fixed-gain relaying and variable-gain relaying schemes. Furthermore, asymptotic results for the SOP are investigated by exploiting the unfolding of Meijer's $G$ -function when the electrical SNR of FSO link approaches infinity. Finally, Monte Carlo simulation results are presented to corroborate the correctness of the analysis.